Numerical comparison of nonstandard schemes for the Airy equation - Adekanye, Oluwaseye; Washington, Talitha (International Journal of Applied Mathematical Research, 2017)
This paper considers the Airy ordinary differential equation (ODE) and different ways it can be discretized. We first consider a standard discretization using the central difference scheme. We then consider two difference schemes which were created using a nonstandard methodology. Finally, we compare the different schemes and how well they approximate solutions to the Airy ODE.